EFFECT OF TOURISM POTENTIAL ON THE DEVELOPMENT OF PAKSEBALI TOURISM VILLAGE, KLUNGKUNG BALI REGENCY - Juniawati, Gaek Raka; Putra, I Dewa Gede Agung Diasana (Universitas Ibn Khaldun Bogor, 2022)
The identity of the village as a tourism village is not only formal, but more than that, it must be able to be accounted for in its operational context. This operational context requires support from all parties so that the sustainability of the tourist village can be maintained. The thing that needs to be considered in the development of a tourist village is the sustainability of its potential. Because the purpose of a tourist village is to provide an opportunity for the community providing tourism to take part in their assets, not just being a spectator to tourism activities whose profits are enjoyed by investors (not local people). Therefore, it is necessary to identify the tourism potential that exists in Paksebali village before making arrangements that pay attention to the hospitality aspect and also the sustainability of natural, cultural and other potentials for the welfare of the local community. The problem that arises in the Paksebali Tourism Village is that the tourist attractions are far apart so that efficient circulation is very important in planning the master plan on a macro basis. And on a micro scale, the need for tourism support facilities that are hospitality and are responsible for the tourism potential available as a sustainable concept.